Bacterial selection and characterization of chitinase enzyme from bacteria controlling Fusarium proliferatum - MIFTAHUL KHAIRAH; NISA RACHMANIA MUBARIK; LISDAR A. MANAF (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Khairah M, Mubarik NR, Manaf LA. 2023. Bacterial selection and characterization of chitinase enzyme from bacteria controlling Fusarium proliferatum. Biodiversitas 24: 1926-1933. The phytopathogenic fungus Fusarium proliferatum causes wilt rot disease of onion bulbs and many agricultural losses. The biocontrol of F. proliferatum can be approached with chitinase from microorganisms, such as endophytic bacteria. The chitinase enzyme can inhibit and control fungus growth by degrading chitin, the main component of the fungal cell wall. This study aimed to select, characterize, and semi-purifying the chitinase produced by endophytic bacteria and to evaluate its antifungal activity against F. proliferatum. The results showed ABS 4.1.2 isolate produced chitinase and had antagonistic activity against F. proliferatum. The prospective ABS 4.1.2 isolate was identified based on 16S rRNA gene as Pseudomonas aeruginosa. The precipitated chitinase using 60% ammonium sulfate (w/v) showed a specific activity of 19.69 U/mg and increased the purity by 3.60 fold. SDS-PAGE analysis showed that chitinase had an estimated molecular weight of 32 kDa and 65 kDa. The chitinase activity of crude extract and precipitated chitinase were optimum at pH 7 and the temperature of 35°C and 45°C, respectively. The precipitated chitinase showed a higher inhibition compared to 12 hrs of cell culture and crude enzymes against F. proliferatum. The precipitated chitinase and crude enzymes significantly exhibited destructive activity toward F. proliferatum mycelium.